2018
DOI: 10.1186/s13054-018-2056-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of optical coherence tomography angiography to assess changes in retinal microcirculation in ovine haemorrhagic shock

Abstract: BackgroundThis study aimed to investigate the feasibility of optical coherence tomography angiography (OCT-A) for quantitative analysis of flow density to assess changes in retinal perfusion in an experimental model of haemorrhagic shock.MethodsHaemorrhagic shock was induced in five healthy, anaesthetized sheep by stepwise blood withdrawal of 3 × 10 ml∙kg− 1 body weight. OCT-A imaging of retinal perfusion was performed using an OCT device. Incident dark-field illumination microscopy videos were obtained for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…In contrast, the manual determination of PVD by OCTA and PVD by IDF focused on the length of microvessels (<20 μm) in an area of interest. However, in this context it is noteworthy that in a recent study we show that automatically calculated retinal flow density showed concordant changes with conjunctival measured PVD by IDF in hemorrhagic shock and resuscitation in sheep 25 . Further studies are needed to investigate the relationship between automatically calculated flow density and manually measured parameters of microcirculatory analysis in critical illness and during interventions in patients.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In contrast, the manual determination of PVD by OCTA and PVD by IDF focused on the length of microvessels (<20 μm) in an area of interest. However, in this context it is noteworthy that in a recent study we show that automatically calculated retinal flow density showed concordant changes with conjunctival measured PVD by IDF in hemorrhagic shock and resuscitation in sheep 25 . Further studies are needed to investigate the relationship between automatically calculated flow density and manually measured parameters of microcirculatory analysis in critical illness and during interventions in patients.…”
Section: Discussionsupporting
confidence: 52%
“…As a result, the use of OCTA in ophthalmic research and clinical practice has become widespread in recent years [15][16][17][18][19][20][21][22][23] . Recent experimental studies have demonstrated the potential usefulness of OCTA for evaluating microcirculatory alternations in critical illness by investigating the microcirculatory changes in the retina during hemorrhagic shock, septic shock and resuscitation 24,25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After ovine haemorrhagic shock [ 123 ], SVP flow density on OCTA decreased from 44.7% baseline to 34.5%, recovering to 46.9% after fluid resuscitation, correlating with systemic haemodynamic parameters. Conjunctival microcirculation assessed using IDF microscopy also showed a reduced proportion of perfused vessels from 100% to 72%, which returned to 98.7% after resuscitation [ 123 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated factors influencing OCTA metrics such as motion artifacts and image quality [1216], age and gender [1722], spherical equivalent and axial length [1325] and systemic diseases [2631] and thereby indicated how to apply and interpret OCTA most adequately. There is very little literature on the influence of mydriasis on quantitative OCTA parameters such as flow density (FD), foveal avascular zone (FAZ), signal strength index (SSI) or motion artifact score (MAS) for image quality.…”
Section: Introductionmentioning
confidence: 99%